Penegakan Hukum Administrasi Terhadap Pelanggaran Perlindungan Dan Pengelolahan Lingkungan Hidup: Studi Kasus Pada PT Karya Citra Nusantara (KCN) DKI Jakarta - Nurainun Nurainun; Ikhsanul Fadly Butar-Butar; Putri Juliani Br Tarigan; Muthia Ivana Zahra; Josua Hery Cristian Gultom (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Every citizen who wants to set up a business must of course comply with the applicable rules and regulations, so that in the future the business will not have a negative impact on society and damage the environment. This research examines administrative law enforcement against violations to protect the environment. The research method used is a normativeempirical research method, which is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents (factually) on each particular legal event that occurs in society. The research results explain that any company that violates applicable regulations and has a negative impact on society, such as impacting public health and impacting the environment, such as environmental pollution, will receive administrative sanctions as stated in government regulations.